Nonuniform Doppler extraction-enhanced multichannel extensive cancellation algorithm for passive radar using Iridium satellite signals - Hongwei Fu; Zhang Zhang; Yu Luo; Tingting Fu; Jianglin Li; Xin Jian; Hao Cha (Scientific Reports)
Abstract Passive radar (PR) relies on receiving signals reflected from targets by other existing noncooperative radiation sources, which are broadly divided into ground- and space-based categories, to achieve target detection and tracking. In the context of space-based PR, this paper proposes a PR using the Iridium satellite signal, which is a low-orbit satellite communication signal with global coverage. With an improved detection range and accredited ambiguity function, a PR using the Iridium satellite signal can address the issues of limited terrestrial coverage for ground-based PR and insufficient receiving power for medium- to high-orbit space-based PR. In addition, to address the problem of multipath clutter broadening caused by the dual movement of low-orbit satellites and the PR receiver, this paper proposes a nonuniform Doppler extraction-enhanced multichannel extensive cancellation algorithm (NuDE-mECA) to suppress multipath clutter broadening while preserving near-field low-speed target detection capabilities. Compared with the traditional multichannel ECA and uniform Doppler extraction multichannel ECA, the NuDE-mECA achieves significantly reduced computational complexity while improving clutter suppression performance and maintaining detection capabilities for low-speed targets. These results provide valuable insights for the lightweight and high-precision design of space-based PR systems.